Exploring the impact of different factors on brand equity and intention to take up online courses from e-Learning platforms. (March 2021) - Ray, Arghya; Bala, Pradip Kumar; Chakraborty, Shibashish; Dasgupta, Shilpee A.
Abstract: Understanding service branding from the customer perspective is helpful for various organizations to attain a competitive edge and build a strong customer base. This research work aims to evaluate the various dimensions and constructs that affect brand equity and user's willingness to undertake courses from various e-Learning providers. Data for the quantitative study was obtained using a questionnaire based survey. Analysis of the 378 responses reveals that consumer experience is a strong predictor of both brand meaning and customer satisfaction. Although brand meaning positively impacts brand equity, brand awareness demonstrates a negative effect on brand equity. However, brand equity and customer satisfaction have a significant and positive impact on intention to undertake courses from online learning platforms. The study concludes with discussion on different implications, shortcomings, and directions for future research. Graphical abstract: Image 1 Highlights: The study explores constructs that affect brand equity and intention to take up online courses. Brand meaning has a positive impact on brand equity. Brand awareness has demonstrated a negative impact on brand equity. Brand equity and customer satisfaction have significant impact on intention to take up online courses.